Hierarchical Coherent Phonons in a Superatomic Semiconductor. Issue 36 (25th July 2019) - Lee, Kihong; Maehrlein, Sebastian F.; Zhong, Xinjue; Meggiolaro, Daniele; Russell, Jake C.; Reed, Douglas A.; Choi, Bonnie; De Angelis, Filippo; Roy, Xavier; Zhu, Xiaoyang
Abstract: The coupling of phonons to electrons and other phonons plays a defining role in material properties, such as charge and energy transport, light emission, and superconductivity. In atomic solids, phonons are delocalized over the 3D lattice, in contrast to molecular solids where localized vibrations dominate. Here, a hierarchical semiconductor that expands the phonon space by combining localized 0D modes with delocalized 2D and 3D modes is described. This material consists of superatomic building blocks (Re6 Se8 ) covalently linked into 2D sheets that are stacked into a layered van der Waals lattice. Using transient reflectance spectroscopy, three types of coherent phonons are identified: localized 0D breathing modes of isolated superatom, 2D synchronized twisting of superatoms in layers, and 3D acoustic interlayer deformation. These phonons are coupled to the electronic degrees of freedom to varying extents. The presence of local phonon modes in an extended crystal opens the door to controlling material properties from hierarchical phonon engineering. Abstract : The superatomic semiconductor, Re6 Se8 Cl2, consists of Re6 Se8 clusters covalently linked into 2D sheets that are stacked into a 3D layered van der Waals lattice. Spectroscopy experiments reveal that vibrational motions can be localized to each 0D building block or delocalized over the 2D and 3D network. This finding opens the door to controlling material properties from hierarchical phonon engineering.